Produk dan Mekanisme Pasar Modal Serta Tata Cara Perdagangan Efek - Handayani, Astutik; Sunarti, Ilis; Atika, Nur; Nurbaiti, Siti; Hendra, Joni (CV. Rayyan Dwi Bharata, 2024)
Capital market is one of market part for many long term financial instrument that can be trade in the capital market. The main instrument of capital market are stock dan obligation. Capital market is a financing equipment for business institution and for other institution, for example the government institution. Those maket also can be use as many investment activities. Thus, the capital market is a market that facilitating various investment equipment and activities that involved a rapid trade activity.